2007
DOI: 10.1890/06-1350.1
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Spatial Structure of a Sri Lankan Tree Species With Multiple Scales of Clustering

Abstract: Clustering at multiple critical scales may be common for plants since many different factors and processes may cause clustering. This is especially true for tropical rain forests for which theories explaining species coexistence and community structure rest heavily on spatial patterns. We used point pattern analysis to analyze the spatial structure of Shorea congestiflora, a dominant species in a 25-ha forest dynamics plot in a rain forest at Sinharaja World Heritage Site (Sri Lanka), which apparently shows cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
238
1
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(256 citation statements)
references
References 33 publications
(49 reference statements)
5
238
1
12
Order By: Relevance
“…Ecologists have argued for the importance of incorporation of spatial scales into the study of ecological processes which underlie spatial patterns because different biological processes may operate at distinguishing spatial scales (Borcard and Legendre 2002;Chase and Leibold 2002;Wiegand et al 2007). Our results support this argument.…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists have argued for the importance of incorporation of spatial scales into the study of ecological processes which underlie spatial patterns because different biological processes may operate at distinguishing spatial scales (Borcard and Legendre 2002;Chase and Leibold 2002;Wiegand et al 2007). Our results support this argument.…”
Section: Discussionmentioning
confidence: 99%
“…Point pattern analysis can help to identify different proximate mechanisms of seed aggregation and to quantify the overall spatial pattern of the seed rain at a range of spatial scales. Thus, a first level of seed aggregation can be quantified by fitting cluster processes (Wiegand et al 2007(Wiegand et al , 2009) to the observed distribution pattern of frugivore regurgitate or fecal samples. However, aggregation of such samples consisting of seeds is not the only potential mechanism of spatially contagious seed dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the effect of landscape structure on the number of steps taken, we used the O-ring statistic, which has been widely used to quantitatively capture the impact of changes in landscape structure on the spatial dynamics of plant and animal species 13 (Bruggeman et al 2010;Wiegand et al 2007;Wiegand et al 1999). The O-ring measures the probability that a habitat cell is located at a distance r from another habitat cell, thus 280 providing a measure of the degree of habitat clustering.…”
mentioning
confidence: 99%